Analysis of the magnetization for Fe and Ni ferromagnetic nanoparticles with variable geometry using VAMPIRE software - Alca-Ramos, Yacu V. (2022)
The purpose of this research is to have a quantitative analysis on the temperature dependence magnetization of ferromagnetic nanoparticles (NPs), i.e., the Curie temperature (Tc), was systematically studied. The atomistic simulations were carried out using the VAMPIRE 5.0 software based on the Landau-Lifshitz-Gilbert-Heun method. The variable parameters of the simulations were damping, time step, particle geometry (spherical, cubic, and cylindrical) and particle size. We have calculated λ for Fe and Ni, in addition we have found different Tc values for each nanogeometry studied following a finite-size effect. We have found ν values for cubic NPs close to the reported values. In particular, it was observed that the Tc values for the studied geometries in the case of Fe and Ni decreases from their theoretical bulk values, for a critical particle size diameter less than 5 nm. Hence, the presented results (optimized atomistic parameters such as simulation time step, damping, and critical exponents) are the basis for advanced simulations of hybrid and complex nanostructures with perspective in biomedical and environmental applications.